HEPATOPROTECTIVE EFFECT OF CHENOPODIUM QUINOA SEED AGAINST CCL4-INDUCED LIVER TOXICITY IN SWISS ALBINO MALE MICE - Saxena, Sneha; Shahani, Lata; Bhatnagar, Pradeep (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: To study the effect of Quinoa seed on carbon tetrachloride (CCL4)-induced liver toxicity in Swiss albino male mice. Methods: Swiss albino male mice were divided into three groups: Group 1 served as control group; Group 2 served as hepatotoxic group (CCl4 treated); and Group 3 served as combination of Quinoa seed powder (20 mg/kg) + CCl4-treated group. The effect of these groups on liver tissue was studied after three different periods of 4, 8, and 12 weeks. Liver marker enzyme level of serum glutamic-oxaloacetic transaminase, serum glutamic-pyruvic transaminase, serum alkaline phosphatase and liver antioxidant enzyme level of lipid peroxidation, superoxide dismutase, and reduced glutathione were measured. Further, histopathological analysis of liver was also conducted. Results: The results showed that the treatment with Quinoa seed powder significantly reduced CCl4-induced elevated serum level of hepatic enzymes and restored the level of liver antioxidant enzymes toward the normal levels, which was also confirmed by histopathological studies. Conclusion: Results of the present study concluded that the Quinoa seed (Chenopodium quinoa) showed hepatoprotective effect against CCl4-induced liver damage in Swiss albino male mice.